STEM-EELS identification of TiOXNY, TiN, Ti2N and O, N dissolution in the Ti2642S alloy oxidized in synthetic air at 650 °C. (June 2019) - Abdallah, Iman; Dupressoire, Charlotte; Laffont, Lydia; Monceau, Daniel; Vande Put, Aurelie
Graphical abstract: Highlights: Ti2 N and oxynitride Phase identification by STEM-EELS technique. Nitrogen environment reduces oxidation kinetics in Ti6242S alloy. Oxynitride/nitride region acts as a diffusion barrier at the interface and reduces oxygen dissolution in the alloy. Oxygen dissolution in Ti6242S oxidized in nitrogen-free atmosphere is more important compared to nitrogen-rich environment. Sn segregation is detected at the oxide-alloy interface in nitrogen-free environment. Abstract: Oxide-alloy interface of Ti6242S Ti-based alloy was investigated by STEM-EELS technique, after oxidation in both N2 -free and synthetic air atmospheres at 650 °C for 1000 h. The chemical shift of Ti-L2, 3 edge and its specific fine structure along the oxide-alloy interface were used as fingerprint to distinguish the different compositions of titanium nitrides and oxynitrides. TiN, Ti2 N and TiNx Oy were identified in the sample oxidized in synthetic air at the oxide-alloy interface. Moreover, a decreasing in the oxidation state of Ti oxides was found along with Sn segregation at the oxide-alloy interface for the sample oxidized in N2 -free atmosphere.